Learning Orientations of Adolescent Dropouts in Sewing Skill Training at BPRSR Yogyakarta - Mulyani, Suci Hari; Sujarwo, Sujarwo (KnE Social Sciences, 2019)
the quality of human resources. Learning orientation contributes to determining the learning outcomes of an educational process. This research paper aims to discover the learning orientation of adolescent dropouts in attending sewing skill training at BPRSR Yogyakarta. This study was a qualitative research using the phenomenological approach conducted at BPRS Yogyakarta. The subject of this study were adolescent dropouts who became participants in sewing skill training. Observation, deep interview, and documentation study were used to collect the data in this research. The result showed that there were three types of participants learning orientations: 1) Skill assignment goal 2) Certificate goal 3) spending time detention goal. Learning orientation affected participants learning outcomes, therefore not ideal orientation needs mental and motivation mentoring. Keywords: Learning Orientation; Adolescent Dropouts; Sewing Skill.